Problematika Pelaksanaan PermenPANRB Nomor 17 Tahun 2021 Tentang Penyetaraan Jabatan Administrasi Ke Dalam Jabatan Fungsional - Ni Kadek Suartini (Jayapangus Press, 2023)
The efficiency of government bureaucracy has long been a topic of debate, with the aspiration of establishing a transparent and authoritative government yet to be realized. State Civil Servants (ASN) are frequently found to be unproductive, neglecting their duties and responsibilities, and lacking in innovation and responsiveness, all of which have hindered progress and advancement. As a response to this issue, the government introduced regulation of the Minister for the Utilization of State Apparatus and Bureaucratic Reform Number 28 of 2019, aimed at simplifying and streamlining the bureaucracy by standardizing administrative positions into functional positions. This regulation was further refined by Regulation of the Minister for the Utilization of State Apparatus and Bureaucratic Reform Number 17 of 2021. However, the implementation of these regulations has been challenging, with numerous issues arising. In order to bring about the desired changes, ongoing studies, analyses, socialization, and the strengthening of apparatus that have undergone standardization are essential. To investigate the problems associated with the implementation of these regulations, this study employs a library research method, utilizing regulations as the primary reference. The findings suggest that the implementation of Regulation of the Minister for the Utilization of State Apparatus and Bureaucratic Reform Number 17 of 2021 has presented significant challenges for both the organization and the functional and structural officials involved.